La storia di Mamadou. Memorie in dialogo sulla frammentazione della vita di un giovane rifugiato - Benemei, Daniela; Scarselli, Francesca; Signorini, Virginia (Antropologia Pubblica, 2017)
In the following pages we propose a patchwork of our memories related to the life of Mamadou, a young refugee who lived and died in Italy. The paper is focusing on the definition of disillusion towards the Italian reception system that not only has been unable to take in charge Mamadou, but became a producer of labels and fragmentation.